The effect of fluid composition on the mechanism of the aragonite to calcite transition - Perdikouri, C.; Kasioptas, A.; Putnis, Christine; Putnis, Andrew (2008)
Experiments were performed to investigate the transformation of natural aragonite crystals to calcite by reaction with aqueous solutions of calcium carbonate at hydrothermal conditions for different periods of time. X-ray powder diffraction (XRD), scanning electron microscopy (SEM), Raman spectroscopy and Laser ablation inductively coupled mass spectrometry (LA-ICP-MS) were used to characterize the reaction product. The results indicate that the replacement of aragonite by calcite follows an interface-coupled dissolution-precipitation mechanism. © 2008 The Mineralogical Society.